2017
DOI: 10.1371/journal.pone.0176880
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide analysis of alternative RNA splicing events in Epstein-Barr virus-associated gastric carcinomas

Abstract: Multiple human diseases including cancer have been associated with a dysregulation in RNA splicing patterns. In the current study, modifications to the global RNA splicing landscape of cellular genes were investigated in the context of Epstein-Barr virus-associated gastric cancer. Global alterations to the RNA splicing landscape of cellular genes was examined in a large-scale screen from 295 primary gastric adenocarcinomas using high-throughput RNA sequencing data. RT-PCR analysis, mass spectrometry, and co-im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 76 publications
0
39
0
Order By: Relevance
“…31 Independent of DNA-level genetic mutations and alterations, alternative splicing represents another process by which a single gene can produce various Cancer February 15, 2020 mRNA and protein isoforms with related, distinct, or even opposing functional differences that can have profound biological consequences. 12,32,33 Using microarray analysis, we confirmed several tumor-specific splice variants of the LAMA3, DST, and TP63 genes in HNSCC, 34 and used RNA sequencing analysis to identify the oncogenic splice variant of AKT3 and DOCK5 in HPV-positive HNSCC and HPV-negative HNSCC, respectively. Alternative RNA splicing is one of the main cellular engines that expands the complexity and diversity of the eukaryotic proteome.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…31 Independent of DNA-level genetic mutations and alterations, alternative splicing represents another process by which a single gene can produce various Cancer February 15, 2020 mRNA and protein isoforms with related, distinct, or even opposing functional differences that can have profound biological consequences. 12,32,33 Using microarray analysis, we confirmed several tumor-specific splice variants of the LAMA3, DST, and TP63 genes in HNSCC, 34 and used RNA sequencing analysis to identify the oncogenic splice variant of AKT3 and DOCK5 in HPV-positive HNSCC and HPV-negative HNSCC, respectively. Alternative RNA splicing is one of the main cellular engines that expands the complexity and diversity of the eukaryotic proteome.…”
Section: Discussionmentioning
confidence: 82%
“…9 The genome-wide mapping of alternative splicing variants also has been identified in a variety of tumors, including gastric, prostate, and breast cancer as well as other tumors. 12,32,33 Using microarray analysis, we confirmed several tumor-specific splice variants of the LAMA3, DST, and TP63 genes in HNSCC, 34 and used RNA sequencing analysis to identify the oncogenic splice variant of AKT3 and DOCK5 in HPV-positive HNSCC and HPV-negative HNSCC, respectively. 15,16 In addition to a specific DOCK5 variant, a total of 580 ASEs associated with HPV-negative HNSCC were determined using outlier analysis, including the specific LOXL2 variant with a novel inserted exon.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Oncogenic viruses have a special relationship with host‐cell AS, as cancer cells present dysregulated AS profiles (David & Manley, ). In the context of cancer, it was demonstrated that EBV‐positive gastric carcinomas showed specific alteration in AS compared to EBV‐negative gastric carcinomas (Armero et al, ). The same conclusion was drawn with hepatitis B (HBV) and hepatitis C virus in hepatocellular carcinomas (Tremblay et al, ).…”
Section: Contribution Of High‐throughput Approachesmentioning
confidence: 99%